2012
DOI: 10.1007/s00167-012-2287-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced morphine consumption and pain severity with transdermal fentanyl patches following total knee arthroplasty

Abstract: Transdermal fentanyl patches provide effective pain relief and decrease total rescue morphine consumption during the first 72 h after operation without additive side effects in patients undergoing TKA surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The KFD combination provides a stable anesthesia and alleviates the tachycardia effect caused by KET. 16,20,43 Moreover, the use of DEX and FENT reduces anesthetic requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The KFD combination provides a stable anesthesia and alleviates the tachycardia effect caused by KET. 16,20,43 Moreover, the use of DEX and FENT reduces anesthetic requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that fentanyl is absorbed rapidly and reaches the maximum serum level in around 2 minutes with few cardiovascular effects without histamine release. It is suggested to be 75–100 times more effective than morphine (14,15). However, fentanyl has several side effects such as nausea and vomiting, bradycardia and respiratory depression, which are often in a dose-related manner (15).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested to be 75–100 times more effective than morphine (14,15). However, fentanyl has several side effects such as nausea and vomiting, bradycardia and respiratory depression, which are often in a dose-related manner (15). Importantly, it has also been reported that fentanyl may protect the heart from post-ischemic injury (16).…”
Section: Introductionmentioning
confidence: 99%
“…Of which 7 studies were excluded due to duplication. The full text was retrieved for the remaining 328 studies, 324 studies were excluded and 4 studies (5,(11)(12)(13) were selected for the final analysis after detailed evaluations.…”
Section: General Characteristic Of the Included Studiesmentioning
confidence: 99%